The immune checkpoint expression in the tumor immune microenvironment of DLBCL: Clinicopathologic features and prognosis - Ma, Jiajia; Pang, Xuelian; Li, Junna; Zhang, Wei; Cui, Wenli (Frontiers in Oncology, 2022)
Background & aims:The immune checkpoint recently provides a new strategy for the immunotherapy of malignant tumors. However, the role in the immune microenvironment of DLBCL is not completely clear. Methods:We detected the expression of PD-1, LAG-3, TIM-3, and TIGIT on TILs and on tumor cells among 174 DLBCL patients by IHC. Results:In TILs, the positive rates of PD-1, LAG-3, TIM-3 and TIGIT were 79.3% , 78.8% , 62.7% and 69.5% , respectively.TIM-3 and TIGIT were expressed in 44.8% and 45.4% of tumor cells. The expression of TIM-3 in TILs was significantly correlated with the Ann-Arbor stage (P=0.039). There was a positive correlation Between PD-1 and LAG-3 or TIM-3 and TIGIT.In addition, LAG-3 expression in TILs was associated with inferior prognosis.Multivariate analysis showed that PS score and R-CHOP therapy were independent risk factors for OS and PFS in patients with DLBCL (P=0.000). Conclusions: The expression level of TIM-3 is closely related to the Ann-Arbor stage, which may be expected to be a new index to evaluate the invasiveness of DLBCL. PD-1 was correlated with the expression of LAG-3, and the high expression of LAG-3 and LAG-3/PD-1 predicted the poor prognosis of DLBCL. Therefore, LAG-3 may become a new target of immunotherapy, or be used in combination with PD-1 inhibitors to improve the drug resistance of current patients with DLBCL.